Still more to learn about late-life cognitive development: how personality and health predict 20-year cognitive trajectories - Wettstein, Markus; Wahl, Hans-Werner; Siebert, Jelena Sophie; Schröder, Johannes (Psychology and aging, 2019)
We examined the role of personality and health as time-invariant and time-varying predictors of changes in different cognitive domains based on data from the Interdisciplinary Longitudinal Study on Adult Development. Our sample consisted of 500 individuals born between 1930 and 1932 (baseline age: M = 62.87 years, SD = 0.89 years) who were assessed up to 4 times over an interval of up to 20 years. Cognitive abilities were measured by multiple well-established tests representing crystallized intelligence. fluid intelligence, and information processing speed. Because of poor psychometric properties of openness in our sample, only 4 of the Big Five personality traits (neuroticism, extraversion. agreeableness, and conscientiousness) were used. Based on in-depth medical examinations, physicians rated study participants' health. When considered as time-invariant predictors, lower baseline neuroticism and extraversion scores were associated with better baseline performance on the crystallized and fluid ability tests. Higher initial extraversion was associated with less steep decline in information processing speed. Worse baseline physician health was associated with lower baseline scores on fluid abilities and information processing speed. Moreover, worse initial health was associated with steeper decline in crystallized and fluid abilities. From a time-varying perspective, crystallized abilities were lower on measurement occasions when individuals revealed poorer health. Our findings suggest that late-life cognitive abilities are differentially related with personality and health. Overall, personality characteristics are associated with late-life cognitive abilities, but less so from a time-varying perspective. They also seem to be of limited importance for the prediction of long-term change in cognitive abilities.